THE GRAMMATICAL ERRORS IN WRITING RECOUNT TEXT AT TENTH GRADE SMA NEGERI 4 PEMATANGSIANTAR - Mardin Silalahi; Dinda Sahputri (Program Studi Pendidikan Bahasa Inggris FKIP, 2021)
This research intended to find out the grammatical errors made by the students at tenth grade SMA Negeri 4 Pematangsiantar in writing recount text. The method of research was qualitative content analysis. The instrument of the research was the writer herself. The sample constituted 36 students or 15% of the total 249 population. The result of this research can be showed as follow: the grammatical errors in writing recount text at tenth grade SMA Negeri 4 Pematangsiantar the error of omission was 46 (35.5%), error of addition was 5 (3.8%), error of mis-formation was 77 (59.2%), and error of disordering was 2 (1.5%). The dominant errors that the students made were error of mis-formation, 77 (59.2%). It could happen because the lack of using simple past tense, misplacement of adjective words, incorrect usage of singular and plural verb, the wrongness of using personal pronoun, limited knowledge of vocabulary, the mistake of using the article, the wrong form of to infinitive verb, and carelessness